2015
DOI: 10.1515/afmnai-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

A Thirty-Seven-Year Follow-Up of Peutz–Jeghers Syndrome across Three Generations / Tridesetsedmogodišnje praćenje Pojc-Jegersovog sindroma kroz tri generacije

Abstract: SU M M A RYPeutz-Jeghers syndrome (PJS) is a rare genetic disorder with autosomal-dominant pleiotropic inheritance, variable penetrance and characteristic signs of the disease that predisposes persons to increased risk of developing cancer, particularly in the gastrointestinal tract and the breast. Due to genetic nature of disease, in the familial Peutz-Jeghers syndrome, a multiplication of symptoms in the three-generation family members was established. This paper represents an insight into the anamnesis of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Also, other appendiceal malignancies (adenocarcinoma) have been found in patients with PJS. [17][18][19][20] In addition, Mojsilovic et al [21] reported a 3-generation family with PJS followed over 37 years. Among others, the authors found endocrine hyperplasia of chromogranin and serotonin-positive cells while some family members had clinically carcinoid-like symptoms [21] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, other appendiceal malignancies (adenocarcinoma) have been found in patients with PJS. [17][18][19][20] In addition, Mojsilovic et al [21] reported a 3-generation family with PJS followed over 37 years. Among others, the authors found endocrine hyperplasia of chromogranin and serotonin-positive cells while some family members had clinically carcinoid-like symptoms [21] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] In addition, Mojsilovic et al [21] reported a 3-generation family with PJS followed over 37 years. Among others, the authors found endocrine hyperplasia of chromogranin and serotonin-positive cells while some family members had clinically carcinoid-like symptoms [21] (Table 1). The link between the PJS and neuroendocrine neoplasms is not clear.…”
Section: Discussionmentioning
confidence: 99%